Challenges Of Humanistic Ski Learning In The Independent Curriculum - Raihanah ZR Lubis; Siti Masitoh; Feni Fitriyah; Peti Rizkiyani; Meirina (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the challenges of implementing humanistic-oriented Islamic Cultural History (SKI) learning within the framework of the Merdeka Curriculum and to identify factors that hinder the realization of meaningful, student-centered, and character-oriented learning. Methodology: This study employed a qualitative approach using library research. Data sources included accredited journal articles, academic books, official curriculum documents, and scientific publications related to Islamic education, humanistic learning, and Islamic Cultural History (SKI) instruction. Data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. Main Findings: The findings reveal four major challenges in implementing humanistic SKI learning: the dominance of rote-learning approaches, limited pedagogical competence among teachers, insufficient contextual learning media and resources, and difficulties in integrating Islamic humanistic values into learning practices. These challenges hinder the development of historical awareness, social sensitivity, critical thinking, empathy, and character development among students. Novelty/Originality of this study: This study contributes a focused analysis of the challenges in implementing humanistic-oriented SKI learning within the Merdeka Curriculum framework. It highlights the relationship between curriculum transformation and the integration of Islamic humanistic values, providing a conceptual basis for strengthening pedagogical competence, developing innovative learning resources, and improving character-oriented Islamic education.